2010
DOI: 10.1111/j.1600-0412.2010.01045.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal hemorrhage in women undergoing elective cesarean section

Abstract: We found no evidence for recommending general screening for FMH in connection with elective cesarean section, provided guidelines such as the current Danish guidelines for Rhesus prophylaxis are followed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…Perslev et al 11 reported a fetomaternal hemorrhage rate of 18.4% in 207 elective cesarean deliveries using flow cytometry, but only 1.4% had a bleed of 5 mL or greater, which was lower than our rate of 14% (13 of 94 study participants). Lubusky et al 7 also used flow cytometry to assess fetomaternal hemorrhage and though they found a higher fetomaternal hemorrhage rate in cesarean delivery compared with vaginal delivery, they only reported a 2.3% rate of a bleed 5 mL or greater with cesarean delivery.…”
Section: Discussioncontrasting
confidence: 74%
“…Perslev et al 11 reported a fetomaternal hemorrhage rate of 18.4% in 207 elective cesarean deliveries using flow cytometry, but only 1.4% had a bleed of 5 mL or greater, which was lower than our rate of 14% (13 of 94 study participants). Lubusky et al 7 also used flow cytometry to assess fetomaternal hemorrhage and though they found a higher fetomaternal hemorrhage rate in cesarean delivery compared with vaginal delivery, they only reported a 2.3% rate of a bleed 5 mL or greater with cesarean delivery.…”
Section: Discussioncontrasting
confidence: 74%
“…The recent prospective study of Uriel and colleagues 19,23 used flow cytometry to determine the volume of FMH during delivery; however, they describe only a small set of patients (n = 346) who were further divided into three groups: vaginal delivery (n = 196), vacuum extraction or forceps delivery (n = 59), and delivery by cesarean section (n = 55). The volume of FMH during delivery ranged from not more than 0.1 to 25.2 mL (mean, 0.25 mL; SD, 1.58 mL), vaginal delivery (mean, 0.12 mL; SD, 0.51 mL; median, 0.03 mL), delivery by cesarean section (mean, 0.67 mL; SD, 3.44 mL; median, 0.03 mL), the difference was statistically significant (p 0.001).…”
Section: Discussionmentioning
confidence: 99%